2018
DOI: 10.3897/neobiota.40.28914
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of invaders has scale-dependent impacts in a changing wetland ecosystem

Abstract: Exotic species are associated with a variety of impacts on biodiversity, but it is unclear whether impacts of exotic species differ from those of native species with similar growth forms or native species invading disturbed sites. We compared presence and abundance of native and exotic invaders with changes in wetland plant species diversity over a 28-year period by re-surveying 22 ponds to identify factors correlated with observed changes. We also compared communities found within dense patches of native and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Although Doss (1993) studied groundwater flows at this site, he did not relate them to vegetation. In a recent resampling of the same dune ponds using the Wilcox and Simonin (1987) study design, Amatangelo et al (2018) showed further changes in plant communities related to invasive species. Paleoecological studies from a much older (>10 K yrs) wetland in this strandplain concluded that major plant-community change during the Holocene resulted from hydrologic change forced by regional climate change (Singer et al 1996).…”
Section: Successional and Hydrological Processesmentioning
confidence: 99%
“…Although Doss (1993) studied groundwater flows at this site, he did not relate them to vegetation. In a recent resampling of the same dune ponds using the Wilcox and Simonin (1987) study design, Amatangelo et al (2018) showed further changes in plant communities related to invasive species. Paleoecological studies from a much older (>10 K yrs) wetland in this strandplain concluded that major plant-community change during the Holocene resulted from hydrologic change forced by regional climate change (Singer et al 1996).…”
Section: Successional and Hydrological Processesmentioning
confidence: 99%